129k views
4 votes
2(3x - 1) + 2(4x + 5) = 8

2 Answers

3 votes

Distribute as we get,


[(3x*2)-(2*1)]+[(4x*2)+(5*2)]=8\\(6x-2)+(8x+10)=8

Remove the brackets,


6x-2+8x+10=8

Then combine,


14x+8=8

Move +8 to the right side and change the +8 to -8 (The operator must be the opposite when move to the other side.)


14x=8-8\\14x=0

Move 14 to the right side so we can find the value of x. (Because it's x multiply 14 then 0 will be divided by 14.)


x=(0)/(14)

Therefore, x = 0.

User Iwona
by
4.7k points
5 votes

Answer:

x=0

Explanation:

2(3x - 1) + 2(4x + 5) = 8

Distribute

6x -2 +8x +10 =8

Combine like terms

14x +8 = 8

Subtract 8 from each side

14x+8-8=8-8

14x =0

Divide each side by 14

14x/14 = 0/14

x=0

User Zack Brown
by
5.1k points